The Effect of Foreign Investment on Domestic Investment In Indonesia - Prasetiadi, Yoga (Efficient: Indonesian Journal of Development Economics, 2021)
The purpose of this study was to analyze the effect of foreign direct investment (FDI) on domestic investment (DI) in Indonesia. The data analysis method in this research was carried out using vector error correction model. Meanwhile, it used secondary data obtained from Statistics Indonesia (BPS) and Ministry of Investment (BKPM). This research period was carried out from 2010-2018. The results of this study indicated that in the long run there was a cointegration relationship between variables, FDI had a significant positive effect on DI in the long and short-term, GDP had a significant negative effect on DI in the long-term. In short-term, it had a negative effect and no significant contribution, structural break down had a positive effect and was not significant in the short-term. The conclusion of this study is that there is a crowding-in relationship between FDI and DI. It is suggested are there should be support from government policies in efforts to improve a more secure investment climate, provide incentives for investors and enforce a clear legal umbrella for investors. Tujuan dari penelitian ini adalah untuk menganalisis pengaruh penanaman modal asing langsung (FDI) terhadap penanaman modal dalam negeri (DI) di Indonesia. Metode analisis data dalam penelitian ini dilakukan dengan menggunakan model koreksi kesalahan vektor. Sedangkan menggunakan data sekunder yang diperoleh dari Badan Pusat Statistik (BPS) dan Kementerian Penanaman Modal (BKPM). Periode penelitian ini dilakukan dari tahun 2010-2018. Hasil penelitian ini menunjukkan bahwa dalam jangka panjang terdapat hubungan kointegrasi antar variabel, FDI berpengaruh positif signifikan terhadap DI dalam jangka panjang dan pendek, PDB berpengaruh negatif signifikan terhadap DI dalam jangka panjang. Dalam jangka pendek berpengaruh negatif dan tidak signifikan, keruntuhan struktural berpengaruh positif dan tidak signifikan dalam jangka pendek. Kesimpulan dari penelitian ini adalah terdapat crowding-in relationship antara FDI dan DI. Disarankan perlu adanya dukungan dari kebijakan pemerintah dalam upaya meningkatkan iklim investasi yang lebih aman, memberikan insentif bagi investor dan menegakkan payung hukum yang jelas bagi investor.